Improving Students' Writing Skills Using Brainstorming at SMP Muhammadiyah 2 Taman - Elanda, Natasha; Novita, Dian (Indonesian Journal Publisher, 2024)
The present study is quantitative research to find out writing skills of the student in descriptive text using brainstorming in the ninth-grade of SMP Muhammadiyah 2 Taman. The components that were analyzed in the descriptive text written by the students were the content of the descriptive text, grammar, and vocabulary. The participants of this research are 25 students in ninth-grade at SMP Muhammadiyah 2 Taman. The aim of this study is to determine whether there is any significance in brainstorming on the descriptive text of writing skills at SMP Muhammadiyah 2 Taman. The result of the study shows that there is a significant effect of brainstorming on the students’ writing achievement. Brainstorming could be an alternative for teaching writing, especially for helping students to learn more about the content, grammar, and vocabulary.